The “canine first technique” in maxillary impacted canines: analysis of the treatment duration and success of therapy - Perrotta, Stefania; Bocchino, Tecla; Amato, Massimo; Michelotti, Ambrosina; Simeon, Vittorio; D’Antò, Vincenzo; Piombino, Pasquale; Carraturo, Emanuele; Vollaro, Stefano; Valletta, Rosa (Frontiers in Oral Health, 2024)
ObjectivesThe goal of the study was to analyze the eruption time of the maxillary impacted canines treated with the “canine first technique” and evaluate the success rate.Materials and methodsA total of 103 patients with 131 impacted canines were treated. Alpha angle, Erickson–Kurol sectors, and age were studied to assess the difficulty of canine eruption. All the canines were treated with the “canine first” approach. The median follow-up time was evaluated using the Kaplan–Meier inverse procedure. The primary outcome (canine eruption time) was analyzed using Kaplan–Meier curves. The curve comparison between the different known risk factors was made using the log-rank test. The median eruption time (95% confidence interval) was calculated for each result.ResultsThe majority of the canines (66.4%) were placed palatally and positioned in sector 3 (30.16%). The median alpha angle was 38.7°. In 88.9% of cases, canines erupted and the median time of eruption was 4.2 months. A statistically significant difference in alpha angle >/<22° able to influence the eruption time was assessed. The variation of the alpha angle (>/<22°) has found to be statistically significative when compared to the eruption time variation.ConclusionThe canine first technique is effective for the eruption of impacted canines, and an alpha angle <22° can be considered a favorable prognostic factor.